MOTION TYPES OF NEUTRAL TEST PARTICLES IN THE FIELD OF CHARGED OBJECT IN GENERAL RELATIVITY AND THEIR CLASSIFICATION - Gladush, V. D.; Kulikov, D. A. (Одеські астрономічні публікації, 2013)
In the previous work of one of the authors the radial motions of charged test particles in the field of a spherically symmetric charged object in general relativity were considered and their classification was built. The present paper generalizes this approach to study the motion of particles with non-zero orbital momentum. We limit the consideration to neutral particles and stress on the peculiarities that emerge in the case of the Reissner-Nordstrom field with superextremal charge.